2018
DOI: 10.1002/jssc.201800585
|View full text |Cite
|
Sign up to set email alerts
|

An HPLC–MS/MS method for the simultaneous determination of luteolin and its major metabolites in rat plasma and its application to a pharmacokinetic study

Abstract: A selective and accurate HPLC-MS/MS method was established to simultaneously quantify luteolin and its active metabolites (diosmetin, chryseriol, and luteolin-7-O-glucuronide) in rat plasma. The analytes were separated on a C column with a mobile phase of water containing 0.5% formic acid and acetonitrile under gradient elution to shorten the total chromatographic run time and increase the resolution of diosmetin and chryseriol. A triple quadruple mass spectrometer coupled with an electrospray ionization sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…Meanwhile, a bimodal phenomenon of 3 flavonoids (daidzein, apigenin, and luteolin) was presented in Figure 4. In accordance with what had been reported previously [36][37][38], the first peak appeared in less than 1 h and the second peak at about 5 h or even later probably due to distribution, reabsorption, and enterohepatic circulation [39][40][41].…”
supporting
confidence: 92%
“…Meanwhile, a bimodal phenomenon of 3 flavonoids (daidzein, apigenin, and luteolin) was presented in Figure 4. In accordance with what had been reported previously [36][37][38], the first peak appeared in less than 1 h and the second peak at about 5 h or even later probably due to distribution, reabsorption, and enterohepatic circulation [39][40][41].…”
supporting
confidence: 92%
“…Luteolin and its metabolites can be efficiently absorbed and show bioactivity after oral administration in rats and humans. In Dong’s study, the quantitative study of rat plasma revealed 3.04 ± 0.60 μg/mL (8.52–12.72 μmol/L) after taking 56.49 mg/kg luteolin . Correspondingly, the rat plasma luteolin concentration of 5–100 μmol/L requires oral administration of 33.27–444.01 mg/kg luteolin.…”
Section: Discussionmentioning
confidence: 99%
“…MRM scanning mode was used on account of the great advantage in selectivity for the quantification of analytes. In the full scan mass spectra, the quasi‐molecular ions [M+H]+ (hypaphorine and abrine) and [M‐H]‐ (schaftoside, isoschaftoside, isoliquiritigenin and luteolin) were stable and in high abundance, and most of them were in good agreement with the literature data . Thus the [M+H]+ and [M‐H]‐ ions were chosen as the precursor ions for MS/MS fragmentation analysis.…”
Section: Resultsmentioning
confidence: 78%